Entre a casa e a escola : prática de atividades físicas e desenvolvimento infantil - Coelho, Vitor Antonio Cerignoni (Universidade Metodista de Piracicaba, 2017)
Among home and school: practice of physical activity and child development Preschoolers are not practicing the minimum of physical activity (PA) according to international guidelines, it has caused the increase of the infant sedentary lifestyle and damages to the integral development. Among the factors which can influence the practice of PA in this age group are people and environments directly involved with children. Thus, the main objective of this research was verifying what parents and teachers think about child development and what way this reflected in the offer physical activities for preschoolers. A field research was done involving 438 adults (197 teachers and 241 parents and guardians of preschool children) from five counties in the metropolitan region of Palmas, the capital of Tocantins State. The participants have answered two questionnaires with 35 questions were about the socio demographic profile, to the activities performed by the children inside and outside of school, a question about what is need for the child development and another about the PA habits. This study has an ecological design and the analysis of the microsystem has showed that the daily frequency of PA inside and outside of school is low (11% and 12%), whereas the activities which can facilitate sedentary behavior were daily offered by 28% and 30% of teachers and parents, respectively. As to necessary aspects for the child development, both groups prioritized the basic necessities, family accompaniment and activities reading, writing, and calculating. The socio demographic profile of the participants has also influenced the offer of the practice of physical activity (age, level education and income). The mesosystem was verified an contradiction between the importance and the daily frequency of PA in the school and home environment, there was also a difference in the answers indicated, which have revealed a discrepancy between the opinion of the parents and teachers. The exosystem has revealed that the PA habits of parents and teachers were associated with indication of the offer of practice for the children. The macrosystem has identified that the poor quality of early childhood education, the lack of PA of the population, the precariousness of professional training programs and beliefs of adults difficult the inclusion the practice of physical activity for preschoolers. The contexts analyzed and the no valorization of the PA as one of the priorities for child development may limit the opportunities of choice and hamper the realization to strategies which reverse the low levels of PA among preschoolers so it is necessary to foster the rapprochement and dialogue between the school and the family.